Hypoxic-Ischemic Encephalopathy and Infantile Spasms - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at UCSF, British Columbia, and Toronto studied the pattern and areas of brain injury on MRI at third day of life of children with infantile spasms following neonatal hypoxic-ischemic encephalopathy (H-IE).